2001
DOI: 10.1089/107999001753124435
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-11 Induces Osteoblast Differentiation and Acts Synergistically with Bone Morphogenetic Protein-2 in C3H10T1/2 Cells

Abstract: Interleukin-11 (IL-11) is a pleiotropic cytokine that supports various types of hematopoietic cell growth and is involved in bone resorption. We report here the involvement of recombinant human IL-11 (rHuIL-11) in osteoblast differentiation in mouse mesenchymal progenitor cells, C3H10T1/2. rHuIL-11 alone increased alkaline phosphatase (ALP) activity and upregulated expression levels of osteocalcin (OC), bone sialo protein (BSP), and parathyroid hormone receptor (PTHR) mRNA. rHuIL-11 had no effect on expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 53 publications
1
30
0
2
Order By: Relevance
“…Other genes found overexpressed in B02 cells (Table 1) include proteoglycan 1 (PRG1), a gene catalogued in the Skeletal Gene Database [40]; interleukin 11 (IL11), a cytokine reported to enhance osteoblast differentiation of mouse mesenchymal progenitors [41] and to act synergically with BMP-2 [42]; and follistatin (FST) that is expressed by chondrocytes and osteoblasts and acts as a local regulator of BMPs function in skeletal cells [43,44]. CTGF, PRG1, IL11 and FST regulation observed in B02 cells is coherent with a previous microarray study [14] that showed an overexpression of these genes in highly bone metastatic MDA-MB-231 subpopulations.…”
Section: Resultsmentioning
confidence: 99%
“…Other genes found overexpressed in B02 cells (Table 1) include proteoglycan 1 (PRG1), a gene catalogued in the Skeletal Gene Database [40]; interleukin 11 (IL11), a cytokine reported to enhance osteoblast differentiation of mouse mesenchymal progenitors [41] and to act synergically with BMP-2 [42]; and follistatin (FST) that is expressed by chondrocytes and osteoblasts and acts as a local regulator of BMPs function in skeletal cells [43,44]. CTGF, PRG1, IL11 and FST regulation observed in B02 cells is coherent with a previous microarray study [14] that showed an overexpression of these genes in highly bone metastatic MDA-MB-231 subpopulations.…”
Section: Resultsmentioning
confidence: 99%
“…142,143 In vitro, IL-11 enhances osteoclast formation and bone resorption, but also stimulates expression of osteoblastic markers in mesenchymal progenitor cells. [144][145][146] During osteogenesis, IL-11 synergizes with BMP-2 in a dose-dependent fashion to enhance the in vitro osteoblastic differentiation of progenitor cells. 146 Although the mechanical properties of the formed bone were not significantly different compared to BMP-2 alone, a similar synergistic increase in bone formation rate was seen after combined implantation of IL-11 and BMP-2 in a rat ectopic and rabbit segmental bone defect model.…”
Section: Cytokinesmentioning
confidence: 99%
“…[144][145][146] During osteogenesis, IL-11 synergizes with BMP-2 in a dose-dependent fashion to enhance the in vitro osteoblastic differentiation of progenitor cells. 146 Although the mechanical properties of the formed bone were not significantly different compared to BMP-2 alone, a similar synergistic increase in bone formation rate was seen after combined implantation of IL-11 and BMP-2 in a rat ectopic and rabbit segmental bone defect model. 147,148 Overall, these results show that IL-11 actions predominantly enhance BMP-2-induced bone formation.…”
Section: Cytokinesmentioning
confidence: 99%
“…IL-11 promotes the maturation of megakaryocytes in vitro (Bruno et al, 1991;Burstein et al, 1992;Teramura et al, 1992;Yonemura et al, 1992) and increases peripheral platelets in myelosuppressed animals (Neben et al, 1993;Yonemura et al, 1993;Nash et al, 1995;Schlerman et al, 1996). IL-11 induces osteoblast differentiation and acts synergistically with BMP-2 in C3H10T1/2 cells (Suga et al, 2001). IL-11 also acts synergistically with BMP-2 to accelerate bone formation in a rat ectopic model (Suga et al, 2003).…”
Section: Discussionmentioning
confidence: 99%